2001
DOI: 10.1038/35074129
|View full text |Cite
|
Sign up to set email alerts
|

Somatic activation of the K-ras oncogene causes early onset lung cancer in mice

Abstract: About 30% of human tumours carry ras gene mutations. Of the three genes in this family (composed of K-ras, N-ras and H-ras), K-ras is the most frequently mutated member in human tumours, including adenocarcinomas of the pancreas ( approximately 70-90% incidence), colon ( approximately 50%) and lung ( approximately 25-50%). To construct mouse tumour models involving K-ras, we used a new gene targeting procedure to create mouse strains carrying oncogenic alleles of K-ras that can be activated only on a spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
820
2
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,059 publications
(861 citation statements)
references
References 23 publications
35
820
2
4
Order By: Relevance
“…using either adenoviral Cre or transgenic systems to induce the expression of mutant K-ras within the lung (Fisher et al, 2001;Jackson et al, 2001;Johnson et al, 2001;Meuwissen et al, 2001). However, the robust nature of inflammation in the CC10-Cre/LSL-K-ras G12D model and the high concentrations of chemotactic substances elaborated by these tumor cells have not been previously reported and therefore provide a unique opportunity to dissect the means by which inflammatory cells are recruited to sites of tumorigenesis, and the roles that these cells play in tumor progression vs suppression.…”
Section: Discussionmentioning
confidence: 99%
“…using either adenoviral Cre or transgenic systems to induce the expression of mutant K-ras within the lung (Fisher et al, 2001;Jackson et al, 2001;Johnson et al, 2001;Meuwissen et al, 2001). However, the robust nature of inflammation in the CC10-Cre/LSL-K-ras G12D model and the high concentrations of chemotactic substances elaborated by these tumor cells have not been previously reported and therefore provide a unique opportunity to dissect the means by which inflammatory cells are recruited to sites of tumorigenesis, and the roles that these cells play in tumor progression vs suppression.…”
Section: Discussionmentioning
confidence: 99%
“…KRAS2 mutations play a causative role in lung cancer development, since transgenic mice carrying an activated KRAS2 gene develop lung cancer early in life and at high frequency (Johnson et al, 2001). In human lung cancer, the presence of KRAS2 mutations is associated with poor prognosis (De Gregorio et al, 1998;Huncharek et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…K-ras mutation has been detected in 70-90% of pancreatic carcinomas, 50% of colorectal carcinomas, and 20-50% of lung carcinomas (Forrester et al, 1987;Rodenhuis et al, 1987;Bos, 1989;Hruban et al, 1993). In tumor cells carrying K-ras mutation, the presence of oncogenic K-Ras is necessary for maintenance of the transformed phenotype (Fisher et al, 2001;Johnson et al, 2001;Meuwissen et al, 2001). Given this, several techniques, such as techniques using farnesyl-transferase inhibitors, antisense oligonucleotides, ribozymes or siRNAs, have been developed to inhibit the activity of Ras (Adjei, 2001;Andreyev et al, 2001;Brummelkamp et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to activation by point mutations, K-ras has been found to be amplified or overexpressed in some cancers (Galiana et al, 1995). Studies using genetically engineered mice have shown that the presence of oncogenic K-ras is not only essential for the initiation of tumorigenesis but also necessary for maintenance of the transformed state (Fisher et al, 2001;Johnson et al, 2001;Meuwissen et al, 2001). Thus, K-Ras is a crucial molecular target in therapeutic strategies to inhibit tumor cell growth.…”
Section: Introductionmentioning
confidence: 99%